Functional characterization of the GWAS lead SNP rs888663 and effects of GDF15 SNPs on GDF15 levels in gestational hypertension and preeclampsia - Daniela A. Pereira; Julyane N. S. Kaihara; Luis Fernando P. Passeti; João Locke F. Araújo; Renan P. Souza; Ana C. Palei; Ricardo C. Cavalli; Chengyu Deng; Nadav Ahituv; Valeria C. Sandrim; Marcelo R. Luizon (Molecular Biology Reports, 2026)
Background Growth differentiation factor 15 (GDF15) is a biomarker for cardiovascular diseases, and its circulating levels are altered in preeclampsia (PE), which shares mechanisms with cardiovascular diseases. Several SNPs in the GDF15 locus were associated with GDF15 levels, including the GWAS lead SNP rs888663. However, no previous study had performed a functional characterization of rs888663 nor had tested the hypothesis that noncoding GDF15 SNPs affect GDF15 levels in PE or gestational hypertension (GH). We examined whether variation of rs888663 affects its enhancer activity, whether genotypes and haplotypes of rs888663 and rs1059369 are associated with PE or GH, and their effects on GDF15 levels in healthy pregnant (HP) women, and in patients with PE and GH. Methods and results We studied 233 HP women, 188 patients with PE, and 197 patients with GH. We performed a dual-luciferase reporter assay testing both rs888663 alleles (G/T), which found that the rs888663 region is a functional enhancer, and the T allele had a significantly higher enhancer activity. Genotypes were determined by Taqman allele discrimination assays. Plasma GDF15 levels were measured by ELISA. GDF15 levels were lower in PE and GH than in HP ( P < 0.01). Patients with PE and GH carrying the TT genotype for rs1059369 and ‘T, T’ haplotype showed lower GDF15 levels than HP women carrying the same genotype and haplotype, respectively ( P < 0.05). Conclusion Our findings identified a novel candidate enhancer of GDF15 , with the rs888663 T allele leading to increased enhancer activity, and suggest that GDF15 SNPs affect GDF15 levels in PE or GH.

Characterizing Airborne Particulate Matter During Late-Season Soybean Production Using SEM/EDX Automated Single Particle Analyses and Machine Learning: A Preliminary Study in the Mississippi Delta - Matthew T. Moore; Lucas J. Heintzman; Juanita Rausch; David Jaramillo-Vogel; Martin A. Locke (Bulletin of Environmental Contamination and Toxicology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Urban tree cover targets: The good, the bad and the SMART - Justin Morgenroth; Kieron Doick; Richard Hauer; Dexter H. Locke; Camilo Ordóñez Barona; Lara A. Roman; Tenley M. Conway; Cynnamon Dobbs; Peter Duinker; Natalie M. Gulsrud; C.Y. Jim; Andrew K. Koeser; et al. (Urban Forestry & Urban Greening, 2025)

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Remarks on the diversity of Hysteromorpha Lutz 1931 (Digenea, Diplostomidae), with erection of a new species from South America - Tyler J. Achatz; Sean A. Locke; Florencia Arrascaeta; Martin M. Montes; Jorge Barneche; Alan Fecchio; Jeffrey A. Bell; Pablo Oyarzún-Ruiz; Geza T. R. Souza; Ricardo M. Takemoto; Vasyl V. Tkach (Systematic Parasitology, 2025)
Hysteromorpha Lutz, 1931 is a small but broadly distributed genus of diplostomoidean digeneans parasitic as adults primarily in cormorants, but also reported from some other fish-eating birds. Their metacercariae were found in a variety of freshwater fishes as second intermediate hosts. Prior to this study, the genus included only 3 nominal species, 2 of them distributed in the Old World and 1 in the New World. We obtained sequences of partial mitochondrial cox 1 gene and nuclear rDNA operon from new specimens collected in Europe, North and South America and used them for species comparisons and phylogenetic analysis. We also examined morphology of our newly collected specimens as well as museum specimens. Our analysis has demonstrated that at least 2 (likely 3) species of Hysteromorpha are distributed in the Americas. Hysteromorpha sp. previously sequenced from larval stages, clearly represents a new species named herein Hysteromorpha ostrowskiae n. sp. Achatz, Locke et Tkach. Morphology of adults of the new species was earlier described in sufficient detail under the name Hysteromorpha triloba (Rudolphi, 1819). Our analyses also suggest the presence of another unknown Hysteromorpha sp. in North America represented by cox 1 sequence from southeastern Canada (GenBank JF769473), but no morphological vouchers are available for this species.

Molecular characterization of a polymycovirus in Leptosphaeria biglobosa - Nesma M. Samir; Jacob Locke-Gotel; Syun-Ichi Urayama; Adel A. El-Morsi; Ghada A. El-Sherbeny; Yongju Huang; Bruce D. L. Fitt; Hiromitsu Moriyama; Robert H. A. Coutts; Ioly Kotta-Loizou (Archives of Virology, 2025)
Leptosphaeria biglobosa is a phytopathogenic ascomycete of Brassica napus that causes phoma stem canker/blackleg. A new double-stranded RNA (dsRNA) mycovirus from this fungus has been fully characterized. The virus genome has five dsRNA segments, ranging in length from 1,180 bp to 2,402 bp. Each dsRNA has a single open reading frame flanked by 5′ and 3′ untranslated regions. The proteins encoded by dsRNAs 1 and 3, an RNA-dependent RNA polymerase (RdRP) and a methyltransferase, respectively, have significant similarity to those of Plasmopara viticola lesion associated polymycovirus 1. The proline-alanine-serine-rich protein encoded by dsRNA 5 is similar to that of Erysiphe necator associated polymycovirus 1. The proteins encoded by dsRNAs 2 and 4 have significant similarity to those of a mycovirus identified in Alternaria sp. FA0703. Phylogenetic analysis based on RdRP sequences showed that this virus clusters with members of the family Polymycoviridae . Based on these observations, this virus, which we have named "Leptosphaeria biglobosa polymycovirus 1", should be classified as a member of the family Polymycoviridae . This is the first report of a polymycovirus in L. biglobosa.

Limitations of existing park quality instruments and suggestions for future research - KangJae “Jerry” Lee; Myla F.J. Aronson; Jeffrey A.G. Clark; Fushcia-Ann Hoover; Hogyeum Evan Joo; Peleg Kremer; Daniele La Rosa; Kelli L. Larson; Christopher A. Lepczyk; Susannah B. Lerman; Dexter H. Locke; Charles H. Nilon; et al. (Landscape and Urban Planning, 2024)

Interactions between management context and tree water use influence stormwater management potential of urban forests - Sarah Ponte; A. Christopher Oishi; Nancy F. Sonti; Dexter H. Locke; Tuana H. Phillips; Mitchell A. Pavao-Zuckerman (Urban Forestry & Urban Greening, 2024)

Echocardiographic and pathologic identification of an aorto-left atrial fistula secondary to infective endocarditis in a canine patient - K. Iuliani; A. Lawler; D. Schrope; E. Locke (Journal of Veterinary Cardiology, 2024)

Measuring the 3-30-300 rule to help cities meet nature access thresholds - M.H.E.M. Browning; D.H. Locke; C. Konijnendijk; S.M. Labib; A. Rigolon; R. Yeager; M. Bardhan; A. Berland; P. Dadvand; M. Helbich; F. Li; H. Li; et al. (Science of The Total Environment, 2024)

Evaluating the Impact of a Culinary Medicine Course on Confidence and Competence in Dietary and Lifestyle Counseling, Interprofessional Communication and Wellness Advocacy and Behaviors - T. Dvorak; B. Retzlaff; A. Locke; T. Petzold (Journal of the Academy of Nutrition and Dietetics, 2023)

Four decades of urban land cover change in Philadelphia - Dexter Henry Locke; Lara A. Roman; Jason G. Henning; Marc Healy (Landscape and Urban Planning, 2023)

183 Effects of prolonged hay net feeding on equine behavior - M.R. Locke; T.D. Cross; A. Hoglan; R. Springer; K.A. Guay; K. Wellmann; R. Martínez; T.N. Jones (Journal of Equine Veterinary Science, 2023)

Can Pesticides Dissolved in Runoff and Exposed to Maturing Rice (Oryza sativa) Plants be Transferred to Seeds? - M. T. Moore; M. A. Locke (Bulletin of Environmental Contamination and Toxicology, 2022)

Transcriptomic and ultrastructural evidence indicate that anti-HMGB1 antibodies rescue organic dust-induced mitochondrial dysfunction - Sanjana Mahadev Bhat; Nyzil Massey; Denusha Shrestha; Locke A. Karriker; Tomislav Jelesijević; Chong Wang; Chandrashekhar Charavaryamath (Cell and Tissue Research, 2022)

Organic dust exposure induces stress response and mitochondrial dysfunction in monocytic cells - Sanjana Mahadev Bhat; Denusha Shrestha; Nyzil Massey; Locke A. Karriker; Anumantha G. Kanthasamy; Chandrashekhar Charavaryamath (Histochemistry and Cell Biology, 2021)

Organic dust-induced mitochondrial dysfunction could be targeted via cGAS-STING or cytoplasmic NOX-2 inhibition using microglial cells and brain slice culture models - Nyzil Massey; Denusha Shrestha; Sanjana Mahadev Bhat; Naveen Kondru; Adhithiya Charli; Locke A. Karriker; Anumantha G. Kanthasamy; Chandrashekhar Charavaryamath (Cell and Tissue Research, 2021)

Beyond ‘trees are good’: Disservices, management costs, and tradeoffs in urban forestry - Lara A. Roman; Tenley M. Conway; Theodore S. Eisenman; Andrew K. Koeser; Camilo Ordóñez Barona; Dexter H. Locke; G. Darrel Jenerette; Johan Östberg; Jess Vogt (Ambio, 2021)

Ontogenetic movements of cod in Arctic fjords and the Barents Sea as revealed by otolith microchemistry - Hector Andrade; Peter van der Sleen; Bryan A. Black; Jane A. Godiksen; William L. Locke; Michael L. Carroll; William G. Ambrose; Audrey Geffen (Polar Biology, 2020)

Experimental Evidence for Using Vegetated Ditches for Mitigation of Complex Contaminant Mixtures in Agricultural Runoff - Matthew T. Moore; Martin A. Locke (Water, Air, & Soil Pollution, 2020)

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

Forest ethnography: An approach to study the environmental history and political ecology of urban forests - Laura A. Ogden; Carissa Aoki; J. Morgan Grove; Nancy Falxa Sonti; William Hall; Dexter Locke; Steward T. A. Pickett; Miriam Avins; Katie Lautar; John Lagrosa (Urban Ecosystems, 2019)

Can Rice (Oryza sativa) Mitigate Pesticides and Nutrients in Agricultural Runoff? - M. T. Moore; M. A. Locke (Bulletin of Environmental Contamination and Toxicology, 2018)

Drying and Storage Methods Affect Cyfluthrin Concentrations in Exposed Plant Samples - M. T. Moore; R. Kröger; M. A. Locke (Bulletin of Environmental Contamination and Toxicology, 2016)

Clinical safety and hypothalamic-pituitary-adrenal axis effects of the arginine vasopressin type 1B receptor antagonist ABT-436 - David A. Katz; Wei Liu; Charles Locke; Sandeep Dutta; Katherine A. Tracy (Psychopharmacology, 2016)

Heat waves imposed during early pod development in soybean ( G lycine max ) cause significant yield loss despite a rapid recovery from oxidative stress - Matthew H. Siebers; Craig R. Yendrek; David Drag; Anna M. Locke; Lorena Rios Acosta; Andrew D. B. Leakey; Elizabeth A. Ainsworth; Carl J. Bernacchi; Donald R. Ort (Global Change Biology, 2015)
Heat waves already have a large impact on crops and are predicted to become more intense and more frequent in the future. In this study, heat waves were imposed on soybean using infrared heating technology in a fully open‐air field experiment. Five separate heat waves were applied to field‐grown soybean ( Glycine max ) in central Illinois, three in 2010 and two in 2011. Thirty years of historical weather data from Illinois were analyzed to determine the length and intensity of a regionally realistic heat wave resulting in experimental heat wave treatments during which day and night canopy temperatures were elevated 6 °C above ambient for 3 days. Heat waves were applied during early or late reproductive stages to determine whether and when heat waves had an impact on carbon metabolism and seed yield. By the third day of each heat wave, net photosynthesis ( A ), specific leaf weight ( SLW ), and leaf total nonstructural carbohydrate concentration ( TNC ) were decreased, while leaf oxidative stress was increased. However, A , SLW , TNC , and measures of oxidative stress were no different than the control ca. 12 h after the heat waves ended, indicating rapid physiological recovery from the high‐temperature stress. That end of season seed yield was reduced (~10%) only when heat waves were applied during early pod developmental stages indicates the yield loss had more to do with direct impacts of the heat waves on reproductive process than on photosynthesis. Soybean was unable to mitigate yield loss after heat waves given during late reproductive stages. This study shows that short high‐temperature stress events that reduce photosynthesis and increase oxidative stress resulted in significant losses to soybean production in the Midwest, U.S. The study also suggests that to mitigate heat wave‐induced yield loss, soybean needs improved reproductive and photosynthetic tolerance to high but increasingly common temperatures.

A Systematic Assessment of the Use of Platelet-Rich Plasma in Spinal Fusion - Benjamin D. Elder; Christina Holmes; C. Rory Goodwin; Sheng-Fu Lo; Varun Puvanesarajah; Thomas A. Kosztowski; John E. Locke; Timothy F. Witham (Annals of Biomedical Engineering, 2015)

A large‐scale molecular survey of Clinostomum (Digenea, Clinostomidae) - Sean A. Locke; Monica Caffara; David J. Marcogliese; Maria L. Fioravanti (Zoologica Scripta, 2015)
Members of the genus Clinostomum Leidy, 1856 are parasites that mature in birds, with occasional reports in humans. Because morphological characters for reliable discrimination of species are lacking, the number of species considered valid has varied by an order of magnitude. In this study, sequences from the DNA barcode region of cytochrome c oxidase I ( CO 1) and/or internal transcribed spacer ( ITS ) from specimens from Mexico, Bolivia, Peru, Brazil, Kenya, China and Thailand were analysed together with published sequences from Europe, Africa, Indonesia and North America. Although ITS and CO 1 distances among specimens were strongly correlated, distance‐based analysis of each marker yielded different groups. Putative species indicated by CO 1 distances were consistent with available morphological identifications, while those indicated by ITS conflicted with morphological identifications in three cases. There was little overlap in sequence variation within and between species, particularly for CO 1. Although ITS and CO 1 distances tended to increase in specimens that were further apart geographically, this did not impair distance‐based species delineation. Phylogenetic analysis suggests a deep division between clades of Clinostomum inhabiting the New World and Old World, which parallels the distribution of their principal definitive hosts, the Ardeidae.

Diazinon and Permethrin Mitigation Across a Grass–Wetland Buffer - M. T. Moore; R. Kröger; M. A. Locke; R. E. Lizotte; S. Testa; C. M. Cooper (Bulletin of Environmental Contamination and Toxicology, 2014)

H alomonas sulfidaeris ‐dominated microbial community inhabits a 1.8 km‐deep subsurface C ambrian S andstone reservoir - Yiran Dong; Charu Gupta Kumar; Nicholas Chia; Pan‐Jun Kim; Philip A. Miller; Nathan D. Price; Isaac K. O. Cann; Theodore M. Flynn; Robert A. Sanford; Ivan G. Krapac; Randall A. Locke; Pei‐Ying Hong; et al. (Environmental Microbiology, 2014)
Summary A low‐diversity microbial community, dominated by the γ ‐proteobacterium H alomonas sulfidaeris , was detected in samples of warm saline formation porewater collected from the C ambrian Mt. S imon S andstone in the I llinois B asin of the N orth A merican M idcontinent (1.8 km/5872 ft burial depth, 50° C , pH 8, 181 bars pressure). These highly porous and permeable quartz arenite sandstones are directly analogous to reservoirs around the world targeted for large‐scale hydrocarbon extraction, as well as subsurface gas and carbon storage. A new downhole low‐contamination subsurface sampling probe was used to collect in situ formation water samples for microbial environmental metagenomic analyses. Multiple lines of evidence suggest that this H . sulfidaeris ‐dominated subsurface microbial community is indigenous and not derived from drilling mud microbial contamination. Data to support this includes V 1‐ V 3 pyrosequencing of formation water and drilling mud, as well as comparison with previously published microbial analyses of drilling muds in other sites. Metabolic pathway reconstruction, constrained by the geology, geochemistry and present‐day environmental conditions of the Mt . S imon S andstone, implies that H . sulfidaeris ‐dominated subsurface microbial community may utilize iron and nitrogen metabolisms and extensively recycle indigenous nutrients and substrates. The presence of aromatic compound metabolic pathways suggests this microbial community can readily adapt to and survive subsurface hydrocarbon migration.

Altered trophic pathway and parasitism in a native predator (Lepomis gibbosus) feeding on introduced prey (Dreissena polymorpha) - Sean A. Locke; Grégory Bulté; David J. Marcogliese; Mark R. Forbes (Oecologia, 2014)

Vulnerability and diet breadth predict larval and adult parasite diversity in fish of the Bothnian Bay - Sean A. Locke; David J. Marcogliese; E. Tellervo Valtonen (Oecologia, 2014)

Effect of Storage Method and Associated Holding Time on Nitrogen and Phosphorus Concentrations in Surface Water Samples - M. T. Moore; M. A. Locke (Bulletin of Environmental Contamination and Toxicology, 2013)

Responses of Phytoplankton and Hyalella azteca to Agrichemical Mixtures in a Constructed Wetland Mesocosm - Richard E. Lizotte; Sam Testa; Martin A. Locke; R. Wade Steinriede (Archives of Environmental Contamination and Toxicology, 2013)

Pharmacokinetics of Levodopa, Carbidopa, and 3-O-Methyldopa Following 16-hour Jejunal Infusion of Levodopa-Carbidopa Intestinal Gel in Advanced Parkinson’s Disease Patients - Dag Nyholm; Per Odin; Anders Johansson; Krai Chatamra; Charles Locke; Sandeep Dutta; Ahmed A. Othman (The AAPS Journal, 2013)

Estimating diet in individual pumpkinseed sunfish Lepomis gibbosus using stomach contents, stable isotopes and parasites - S. A. Locke; G. Bulté; M. R. Forbes; D. J. Marcogliese (Journal of Fish Biology, 2013)
The diets of 99 pumpkinseed sunfish Lepomis gibbosus from a pair of small, adjacent lakes in Ontario, Canada, were estimated from their stomach contents, trophically transmitted parasites and stable isotopes of carbon and nitrogen in fish tissue. The three methods provided virtually unrelated information. There was no significant correlation in the importance of any prey item across all three methods. Fish with similar diets according to one method of estimating diet showed no tendency to be similar according to other methods. Although there was limited variation in fish size and the spatial scale of the study was small, both fish size and spatial origin showed comparatively strong associations with diet data obtained with all three methods. These results suggest that a multidisciplinary approach that accounts for fish size and spatial origins is necessary to accurately characterize diets of individual fish.

Potential for Phosphate Mitigation from Agricultural Runoff by Three Aquatic Macrophytes - H. L. Tyler; M. T. Moore; M. A. Locke (Water, Air, & Soil Pollution, 2012)

Phytotoxicity of Atrazine, S-Metolachlor, and Permethrin to Typha latifolia (Linneaus) Germination and Seedling Growth - M. T. Moore; M. A. Locke (Bulletin of Environmental Contamination and Toxicology, 2012)

Influence of Three Aquatic Macrophytes on Mitigation of Nitrogen Species from Agricultural Runoff - Heather L. Tyler; Matthew T. Moore; Martin A. Locke (Water, Air, & Soil Pollution, 2012)

The scopolamine model as a pharmacodynamic marker in early drug development - Robert A. Lenz; Jeffrey D. Baker; Charles Locke; Lynne E. Rueter; Eric G. Mohler; Keith Wesnes; Walid Abi-Saab; Mario D. Saltarelli (Psychopharmacology, 2012)

Regional differences in foraging behaviour of invasive green crab (Carcinus maenas) populations in Atlantic Canada - Melanie A. Rossong; Pedro A. Quijón; Paul V. R. Snelgrove; Timothy J. Barrett; Cynthia H. McKenzie; Andrea Locke (Biological Invasions, 2012)

Bolder Thinking for Conservation - REED F. NOSS; ANDREW P. DOBSON; ROBERT BALDWIN; PAUL BEIER; CORY R. DAVIS; DOMINICK A. DELLASALA; JOHN FRANCIS; HARVEY LOCKE; KATARZYNA NOWAK; ROEL LOPEZ; CONRAD REINING; STEPHEN C. TROMBULAK; et al. (Conservation Biology, 2012)

Effects of Vegetation in Mitigating the Toxicity of Pesticide Mixtures in Sediments of a Wetland Mesocosm - Richard E. Lizotte; Matthew T. Moore; Martin A. Locke; Robert Kröger (Water, Air, & Soil Pollution, 2011)

Role of Vegetation in a Constructed Wetland on Nutrient–Pesticide Mixture Toxicity to Hyalella azteca - Richard E. Lizotte; Matthew T. Moore; Martin A. Locke; Robert Kröger (Archives of Environmental Contamination and Toxicology, 2011)

DNA barcodes show cryptic diversity and a potential physiological basis for host specificity among Diplostomoidea (Platyhelminthes: Digenea) parasitizing freshwater fishes in the St. Lawrence River, Canada - SEAN A. LOCKE; J. DANIEL MCLAUGHLIN; DAVID J. MARCOGLIESE (Molecular Ecology, 2010)
Diplostomoid metacercariae parasitize freshwater fishes worldwide and cannot be identified to species based on morphology. In this study, sequences of the barcode region of cytochrome c oxidase subunit 1 (CO1) were used to discriminate species in 1088 diplostomoids, most of which were metacercariae from fish collected in the St. Lawrence River, Canada. Forty‐seven diplostomoid species were detected, representing a large increase in known diversity. Most species suggested by CO1 sequences were supported by sequences of internal transcribed spacer (ITS) of rDNA and host and tissue specificity. Three lines of evidence indicate that physiological incompatibility between host and parasite is a more important determinant of host specificity than ecological separation of hosts and parasites in this important group of freshwater fish pathogens. First, nearly all diplostomoid species residing outside the lens of the eyes of fish are highly host specific, while all species that occur inside the lens are generalists. This can be plausibly explained by a physiological mechanism, namely the lack of an effective immune response in the lens. Second, the distribution of diplostomoid species among fish taxa reflected the phylogenetic relationships of host species rather than their ecological similarities. Third, the same patterns of host specificity were observed in separate, ecologically distinctive fish communities.

An isobaric–isenthalpic magma mixing model for the Hasan Dagi volcano, Central Anatolia, Turkey - A. Umran Dogan; Meral Dogan; Attila Kilinc; Darren Locke (Bulletin of Volcanology, 2008)

Tillage and cover effects on soil microbial properties and fluometuron degradation - Robert M. Zablotowicz; Martin A. Locke; Lewis A. Gaston (Biology and Fertility of Soils, 2007)

Diazinon Mitigation in Constructed Wetlands: Influence of Vegetation - M. T. Moore; C. M. Cooper; S. Smith; R. F. Cullum; S. S. Knight; M. A. Locke; E. R. Bennett (Water, Air, & Soil Pollution, 2007)

Local Enhancement in Mud-Puddling Swallowtail Butterflies (Battus philenor and Papilio glaucus) - G.W. Otis; B. Locke; N.G. McKenzie; D. Cheung; E. MacLeod; P. Careless; A. Kwoon (Journal of Insect Behavior, 2006)

Land Use Influences and Ecotoxicological Ratings for Upper Clinch River Tributaries in Virginia - B. A. Locke; D. S. Cherry; C. E. Zipper; R. J. Currie (Archives of Environmental Contamination and Toxicology, 2006)

Profiling penciclovir susceptibility and prevalence of resistance of herpes simplex virus isolates across eleven clinical trials - R. T. Sarisky; T. H. Bacon; R. J. Boon; K. E. Duffy; K. M. Esser; J. Leary; L. A. Locke; T. T. Nguyen; M. R. Quail; R. Saltzman (Archives of Virology, 2003)

Geochemical Behavior of Arsenic in Kelly Lake, Ontario - Muhammad Sadiq; Allen Locke; Grame Spiers; David A. B. Pearson (Water, Air, & Soil Pollution, 2002)

Will reduced summer UV-B levels affect zooplankton populations of temperate humic and clearwater lakes?* - T.A. Clair; J. Ehrman; I. Kaczmarska; A. Locke; D.W. Tarasick; K.E. Day; G. Maillet (Hydrobiologia, 2001)

Genomic organization of the rat α 2u -globulin gene cluster - David A. McFadyen; William Addison; John Locke (Mammalian Genome, 1999)

Effect of seed piece size on performance of three potato varieties in the Klamath Basin of Oregon - K. A. Rykbost; K. A. Locke (American Journal of Potato Research, 1999)

Identification by physical means of organic moieties of conjugates produced from carbaryl by tobacco cells in suspension culture - Raymond K. Locke; Jo -Yun T. Chen; Joseph N. Damico; Laurence R. Dusold; James A. Sphon (Archives of Environmental Contamination and Toxicology, 1976)

Heat inactivation of leafroll virus in potato tuber tissues - A. Hamid; S. B. Locke (American Journal of Potato Research, 1961)